Modeling RBE‐weighted dose variations in irregularly moving abdominal targets treated with carbon ion beams. Issue 7 (18th April 2020) - Meschini, Giorgia; Kamp, Florian; Hofmaier, Jan; Reiner, Michael; Sharp, Gregory; Paganetti, Harald; Belka, Claus; Wilkens, Jan J.; Carlson, David J.; Parodi, Katia; Baroni, Guido; Riboldi, Marco
Abstract : Purpose: To model four‐dimensional (4D) relative biological effectiveness (RBE)‐weighted dose variations in abdominal lesions treated with scanned carbon ion beam in case of irregular breathing motion. Methods: The proposed method, referred to as bioWED method, combines the simulation of tumor motion in a patient‐ and beam‐specific water equivalent depth (WED)‐space with RBE modeling, aiming at the estimation of RBE‐weighted dose changes due to respiratory motion. The method was validated on a phantom, simulating gated and free breathing dose delivery, and on a patient case, for which free breathing irradiation was assumed and both amplitude and baseline breathing irregularities were simulated through a respiratory motion model. We quantified (a) the effect of motion on the equivalent uniform dose (EUD) and the RBE‐weighted dose–volume histograms (DVH), by comparing the planned dose distribution with "ground truth" 4D RBE‐weighted doses computed using 4D computed tomography data, and (ii) the estimation error, by comparing the doses estimated with the bioWED method to "ground truth" 4D RBE‐weighted doses. Results: In the phantom validation, the estimation error on the EUD was limited with respect to the motion effect and the median estimation error on relevant RBE‐weighted DVH metrics remained within 5%. In the patient study, the estimation error as computed on the EUD was smaller than the corresponding motion effect, exhibiting the largest values in the baseline irregularity simulation. However, the median estimation error over all simulations was below 3.2% considering relevant DVH metrics. Conclusions: In the evaluated cases, the bioWED method showed proper accuracy when compared to deformable image registration‐based 4D dose calculation. Therefore, it can be seen as a tool to test treatment plan robustness against irregular breathing motion, although its accuracy decreases as a function of increasing soft tissue deformation and should be evaluated on a larger patient dataset.